2013
DOI: 10.1186/1742-2094-10-98
|View full text |Cite
|
Sign up to set email alerts
|

T-cell reconstitution during murine acquired immunodeficiency syndrome (MAIDS) produces neuroinflammation and mortality in animals harboring opportunistic viral brain infection

Abstract: BackgroundHighly active antiretroviral therapy (HAART) restores inflammatory immune responses in AIDS patients which may unmask previous subclinical infections or paradoxically exacerbate symptoms of opportunistic infections. In resource-poor settings, 25% of patients receiving HAART may develop CNS-related immune reconstitution inflammatory syndrome (IRIS). Here we describe a reliable mouse model to study underlying immunopathological mechanisms of CNS-IRIS.MethodsUtilizing our HSV brain infection model and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Many other ART formulations have demonstrated a capacity for neurotoxicity as well; a systematic analysis of in vitro effects of 15 antiretroviral compounds, including nucleoside reverse transcriptase inhibitors (NRTIs), NNRTIs and protease inhibitors (PIs) on neurons found a wide range of neurotoxic mechanisms, such as mitochondrial toxicity, with the ultimate endpoint of neuronal dysfunction (Robertson et al 2012). Alternatively, neuroinflammation in the CC may be secondary to the immune reconstitution following ART initiation, which has been observed in animal models (Mutnal et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Many other ART formulations have demonstrated a capacity for neurotoxicity as well; a systematic analysis of in vitro effects of 15 antiretroviral compounds, including nucleoside reverse transcriptase inhibitors (NRTIs), NNRTIs and protease inhibitors (PIs) on neurons found a wide range of neurotoxic mechanisms, such as mitochondrial toxicity, with the ultimate endpoint of neuronal dysfunction (Robertson et al 2012). Alternatively, neuroinflammation in the CC may be secondary to the immune reconstitution following ART initiation, which has been observed in animal models (Mutnal et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Peripherally, LP-BM5 is marked by splenomegaly, lymphadenopathy, and hypergammaglobulinemia similar to HIV-1. Suppressed B- and T-cell responses paired with a loss of CD4 + T-cell function induce the HIV-1-like state termed murine AIDS (Li and Green, 2006); recently, Mutnal et al observed a profound loss of circulating CD4 + and CD8 + T-cells in LP-BM5 animals, similar to HIV-1 patients (Mutnal et al, 2013). Altogether, LP-BM5/MAIDS offers the opportunity to explore morphine’s effects within the context of an immunodeficiency-inducing virus which infiltrates the CNS, infects glial cells, and produces established effects on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-g production by the reconstituting CD4 T cells, which is normally required for containment of mycobacterial infection, is a major mediator of the disease in this setting. Models of IRIS associated with other microbial infections (Roths et al 1990;Sidman 1992, 1993;Bhagwat et al 2006;Mutnal et al 2013) have also found that in the setting of immune reconstitution, CD4 T cells can mediate severe immunopathology. Collectively, the data from studies of IRIS in HIV-coinfected individuals and the experimental animal model data strongly support the hypothesis that IRIS in humans is mediated by CD4 T cells and provide another example of CD4 T-cell-mediated pathology in mycobacterial infection.…”
Section: Immune Reconstitution Inflammatory Syndromementioning
confidence: 99%